PENGARUH TINGKAT KESEHATAN BANK BERDASARKAN METODE RGEC TERHADAP RETURN SAHAM PADA PERUSAHAAN PERBANKAN DI BURSA EFEK INDONESIA TAHUN 2010-2013 (Students' Journal of Accounting and Banking, 2015)
This study aims to analyze and test the effect of the bank based methods rgec on stock returns in the banking company on the stock exchange Indonesia 2010-2013. The population in this study is a banking company that is listed on the stock exchange Indonesia 2010-2013. The sampling technique using purposive sampling method. Hypothesis testing using multiple linear regression analysis with the Statistical Product and Service Solutions. Hypothesis testing results prove that the credit risk and liquidity risk significant negative effect on stock returns. Market risk and earning is not a significant positive effect on stock returns. Good corporate governance and capital is not a significant negative effecton stock returns.Keywords: Credit Risk, Liquidity Risk, Market Risk, Corporate Governance, Earnings, and Capital, Stock Returns